Rational Emotive Behavior Therapy (REBT), Irrational and Rational Beliefs, and the Mental Health of Athletes - Turner, Martin J. (Frontiers in Psychology, 2016)
In this article Rational Emotive Behavior Therapy (REBT) is proposed as a potentially important framework for the understanding and promotion of mental health in athletes. Cognitive-behavioral approaches predominate in the provision of sport psychology, and often form the backbone of psychological skills training (PST) for performance enhancement and maintenance. But far from being solely performance-focused, the cognitive-behavioral approach to sport psychology can restore, promote, and maintain mental health. This review article presents REBT (Ellis, 1957), the original cognitive behavioral therapy (CBT), as a valuable approach to addressing mental health issues in sport. REBT holds that it is not events that directly cause emotions and behaviors. Rather, it is one’s beliefs about the events that lead to emotional and behavioral reactivity. Further, REBT distinguishes between rational and irrational beliefs, and suggests that in response to failure, maltreatment, and misfortune, people can react with either healthy or unhealthy emotional and behavioral responses. The extant research indicates that irrational beliefs lead to unhealthy negative emotions, a range of pathological conditions, and a host of maladaptive behaviors that undermine mental health. Therefore, REBT proposes a process for the reduction of irrational beliefs and the promotion of rational beliefs. The use of REBT in sport is seldom reported in literature, but research is growing. This review article proposes three important areas of investigation that will aid the understanding of irrational beliefs and the application of REBT within sport. These areas are: (1) the influence of irrational beliefs and REBT on the mental health of athletes, (2) the influence of irrational beliefs and REBT on athletic performance, (3) the origins and development of irrational beliefs in athletes. Each area is discussed in turn, offering a critical and progressive review of the literature as well as highlighting research deficits, and recommendations to address each of the three areas of investigation.